Healthy but not RSV-infected lung epithelial cells profoundly inhibit T cell activation. Issue 4 (18th August 2008) - Wang, H; Su, Z; Schwarze, J
Abstract : Background: Respiratory viruses, including respiratory syncytial virus (RSV), can cause asthma exacerbations and bronchiolitis. Both conditions are associated with enhanced cognate immune responses and inflammation and reduced immune regulation. Lung epithelial cells (LECs) can contribute to antiviral and allergic immune responses while gut epithelial cells can inhibit effector T cell responses. A study was performed to determine whether healthy LECs regulate antigen-specific T cell responses and if this regulation is lost during RSV infection. Methods: LA4 cells, a murine LEC line, infected with RSV or primary murine LECs were co-cultured with ovalbumin-specific T cell receptor transgenic CD4+ T cells from DO11.10 mice and ovalbumin-pulsed bone marrow-derived dendritic cells (DC) to assess T cell proliferation by flow cytometry and cytokine production. Results: The presence of LECs abrogated DC-induced T cell proliferation and significantly reduced T cell cytokine release. These effects of LECs were predominantly contact-dependent, primarily affected T cells directly and were partly mediated by transforming growth factor β. Soluble factors and DC-mediated effects also contributed to T cell inhibition. RSV infection of LECs reduced their inhibitory capacity in an infection dose-dependent manner. This was independent of proinflammatory cytokines released by infected LECs, but in part due to Toll-like receptor activation and to infection-induced cell death. Conclusion: Healthy LECs are potent inhibitors of T cell activation, but this regulatory function is lost after RSV infection. These findings suggest a central role for LECs in maintaining the tolerogenic environment of healthy lungs. Loss of this regulatory capacity after viral infection may allow development of excessive cognate immune responses and pulmonary inflammation.